Performance Evaluation of UDSM Network to Deliver Multimedia eLearning Contents: Case of CoICT - Mercy, Mbise; Fatuma, Simba (Tanzania Journal of Engineering and Technology, 2023)
The use of technology in education in Sub-Saharan Africa has been reported to be hindered by many factors including inadequate Information and Communication Technology (ICT) infrastructure, low internet speed, and lack of skills to use educational technologies. This paper aim at evaluating how the available ICT infrastructure at the College of Information and Communication Technologies (CoICT) can support, with acceptable Quality of Service (QoS), the delivery of multimedia applications for eLearning services. The evaluation was performed over a network testbed implemented in a computer laboratory for wired and wireless connections. The testbed consisted of five personal computers (PCs) connected via a switch and a router to the internet for the wired connection. The wireless connection consisted of three PCs and a laptop connected through a switch and a router to the internet via a wireless access point. Four different multimedia applications were run through the PCs, and traffic data was mirrored and captured at one of the PC using Wireshark network analyzer. The traffic included streamed and conversational video and audio using YouTube and Zoom applications, respectively; interactive web browsing using web browsers; bulk file transfer, and a mixture of all applications running on the computers. Traffic data captured during the running of these applications were packet loss, delay, jitter, and throughput. The QoS performance parameters obtained were within the acceptable threshold values as per International Telecommunication Union, Telecommunication Standardization Sector (ITU-T) values. Results revealed that ICT infrastructure at CoICT can support delivery of multimedia content for eLearning purposes for both wired and wireless connections. Having the infrastructure capable of supporting multimedia applications with the acceptable QoS implies that instructors are equipped with a conducive environment that supports multimedia application. Hence, they are expected to use and continue using educational technologies to facilitate teaching and learning processes. Keywords: Multimedia, network testbed, Quality of Service (QoS), e-learning, higher learning institution (HEI).